Short Communication: Duration and volume of crowing of Pelung chickens of West Java, Indonesia - INDRAWATI Y. ASMARA; DANI GARNIDA; Ruhyat Partasasmita (Society for Indonesian Biodiversity, 2020)
Abstract. Asmara IY, Garnida D, Partasasmita R. 2020. Short Communication: Duration and volume of crowing of Pelung chickens of West Java, Indonesia. Biodiversitas 21: 748-752. Pelung are long crowing chickens originally from West Java Province, Indonesia. The chickens are raised as singing birds due to their beautiful crowing capability. Nowadays, the chickens are distributed not only in West Java, Indonesia but also in other provinces in Indonesia because of the existence of Pelung contests. The contests evaluate singing ability of Pelung chickens and are important promotion media for the birds. In contests, crowing characteristics such as duration and intensity are important factors to determine the quality of chickens. Some factors such as age, body weight, and body morphometrics are assumed to influence crowing characteristics. The study was aimed to determine crowing duration and volume in Pelung roosters, as well as correlations of age, body weight and body morphometrics with crowing characteristics. A survey was performed to collect data involving 73 birds in two areas in West Java Province. The research locations are Cianjur and Sukabumi Districts. The results showed that roosters in all areas have similar crowing durations, while their crowing intensities are varied. The study also found that age and body weight, as well as some body-morphometries, have strong correlations with crowing characteristics. The research provides empirical evidence of factors determining vocal performance of Pelung chickens. However, more samples from different areas are required to support these findings. In addition, research on management systems, health status and participation of chickens in rehearsal is needed in the future.